MERANGKUL EMOSI UNTUK HIDUP LEBIH BERMAKNA: PSIKOEDUKASI EMOSI DAN EKSPRESINYA DI LKSA SINGARAJA, BALI - Princen Princen; Nurtaty Sinaga; Krishervina Rani Lidiawati; Careninna Angela Wongkar; Yoan Karina; Aretha Christabel (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Adolescents living in Child Welfare Institutions (LKSA) often face challenges in recognizing and expressing their emotions. This Community Service (PkM) initiative aimed to enhance emotional competence among 56 adolescents at LKSA Widhya Asih Singaraja, Bali, through psychoeducational sessions. Conducted five times over five months, the program covered emotional awareness, empathy, and regulation. Pre- and post-test evaluations revealed no statistically significant improvements in emotion regulation. Nevertheless, qualitative feedback indicated participants’ enthusiasm and a positive perception of the material. The psychoeducation sessions were found to be communicative and relevant, although greater impact may be achieved with extended duration and frequency.